2017
DOI: 10.3389/fpsyg.2017.02014
|View full text |Cite
|
Sign up to set email alerts
|

Pacifier Overuse and Conceptual Relations of Abstract and Emotional Concepts

Abstract: This study explores the impact of the extensive use of an oral device since infancy (pacifier) on the acquisition of concrete, abstract, and emotional concepts. While recent evidence showed a negative relation between pacifier use and children's emotional competence (Niedenthal et al., 2012), the possible interaction between use of pacifier and processing of emotional and abstract language has not been investigated. According to recent theories, while all concepts are grounded in sensorimotor experience, abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 73 publications
5
62
0
Order By: Relevance
“…Finally, the interpretation of the findings is further complicated by evidence linking dummy use with lower socioeconomic status (Gale and Martyn, 1996;Fleming et al, 1999;Mauch et al, 2012; see also Whitmarsh, 2008). Complementing the findings of Gale and Martyn (1996) and Barca et al (2017) have recently showed an association between prolonged (>3 years) use of pacifiers during social interactions with a child's difficulties in distinguishing abstract and concrete concepts at the ages of six to seven. In addition, in the study by Lehman et al (1992), American infants showing a long-term preference for using pacifiers for comfort were less likely to be securely attached to their mothers than infants with a preference for soft objects.…”
Section: What's Dummy Got To Do With It?mentioning
confidence: 91%
See 1 more Smart Citation
“…Finally, the interpretation of the findings is further complicated by evidence linking dummy use with lower socioeconomic status (Gale and Martyn, 1996;Fleming et al, 1999;Mauch et al, 2012; see also Whitmarsh, 2008). Complementing the findings of Gale and Martyn (1996) and Barca et al (2017) have recently showed an association between prolonged (>3 years) use of pacifiers during social interactions with a child's difficulties in distinguishing abstract and concrete concepts at the ages of six to seven. In addition, in the study by Lehman et al (1992), American infants showing a long-term preference for using pacifiers for comfort were less likely to be securely attached to their mothers than infants with a preference for soft objects.…”
Section: What's Dummy Got To Do With It?mentioning
confidence: 91%
“…Are pacifiers more likely to affect infants' competences in specific time periods? Such a possibility is hinted to in the study of Barca et al (2017), in which children who used pacifiers for more than 3 years and during social interactions showed impairments in their ability to discriminate between concrete and abstract concepts. Finally, as mentioned earlier, babies' responses to facial expressions are only part of a dynamic system involving both the infant and the caregiver (Tronick, 1989;Meltzoff, 1990;Fogel et al, 1992) and, in order to understand the long-term effects of pacifier use it is necessary to examine how dummies influence natural interactions between babies and caregivers.…”
Section: Where Do We Go From Here?mentioning
confidence: 99%
“…Ratings 581 results showed that emotional concepts activate both the mouth and the hand effectors, while 582 mental states concepts activate more selectively the mouth (Ghio et al, 2013), andfMRI results 583 clearly demonstrated that while the face/mouth motor system in the brain is more activated by more 584 pure abstract concepts as mental state concepts than by emotional ones, which activate hand and 585 face motor cortex to similar degrees (Dreyer and Pulvermuller, 2017). Overall, this finding is in 586 line with views according to which emotions represent a third kind of concepts, structurally 587 different from both concrete and abstract ones (see Barca et al, 2017, andMazzuca et al, 2017, 588 for further discussion), and with the proposal according to which emotional concepts, being more 589 grounded than other abstract concepts, provide a bootstrapping mechanism to learn them (Ponari 590 et al, 2017). 591 592…”
Section: Introduction 24 25supporting
confidence: 55%
“…Children in the control groups were selected from a pool of 73 TD children who completed both tasks: 18 children (14 males; mean age ¼ 10. 34 [22]; TD voc ). TD children were recruited from local schools and did not have any reported special educational needs, or history of language delay.…”
Section: Methods (A) Participantsmentioning
confidence: 99%
“…(c) Definitions' conceptual features. Definitions were scored based on the 11 conceptual categories used by Barca et al [34]. This classification allows us to have some initial insight on whether the conceptual features of concepts known by DLD and TD children differ.…”
Section: (Ii) Definitionmentioning
confidence: 99%